Enhancing university teaching and learning through integration of artificial intelligence in information and communication technology - Alzakwani, Mujahid Hamood Hilal; Zabri, Shafie Mohamed; Ali, Rabei Raad (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of Artificial Intelligence (AI) integrated into Information and Communications Technology (ICT) in higher education to improve teaching and learning outcomes. Through the analysis of case studies, the study delves into how AI influences teaching, learning, and overall educational processes. It examines the role of AI in higher education, its potential areas for improvement, and the challenges campus planners face in adopting AI within the ICT framework. AI integration in educational settings aims to develop adaptive learning systems tailored to individual student needs, fostering engagement and clarity in understanding. AI facilitates personalized learning paths and resources based on comprehensive data analysis, moving away from generic instructional materials. Real-time feedback from AI-powered assessment tools aids in continuous learning and lightens the workload for teachers, enhancing teaching quality. Additionally, AI-driven ICT solutions offer analytical tools for data-informed decision-making by administrators, optimizing educational outcomes. However, the integration of AI in higher education poses challenges such as ethical concerns, data privacy issues, and the necessity of faculty training. Overcoming these challenges requires careful planning, policy development, and collaboration between educators, technologists, and policymakers.